Using nonlinear dynamics analysis to evaluate time response of cupping therapy with different intervention timings on reducing muscle fatigue - Jia, Yuanyuan; Liu, Yining; Lei, Juntian; Wang, Huihui; Wang, Rong; Zhao, Pengrui; Sun, Tingting; Hou, Xiao (Frontiers in Bioengineering and Biotechnology, 2024)
Background Cupping therapy has been indicated effective in reducing muscle fatigue after 24 h based on the spectral analyses of surface electromyography (sEMG). However, there is no sufficient evidence showing changes of sEMG nonlinear indexes at more time points after cupping therapy. Furthermore, it is unclear whether the intervention timings of cupping therapy affect the recovery from muscle fatigue. The purpose of this study was to use the sEMG nonlinear analysis to assess the difference of time response of cupping therapy between different intervention timings after muscle fatigue. Materials and methods This randomized controlled trial recruited 26 healthy volunteers. Cupping therapy (−300 mmHg pressure for 5 min by the 45 mm-diameter cup) was applied before (i.e., pre-condition) or after (i.e., post-condition) muscle fatigue induced by performing repeated biceps curls at 75% of the 10 repetitions of maximum (RM) on the non-dominant upper extremity. Subjects were randomly allocated to the pre-condition group or the post-condition group. The sEMG signals during the maximal voluntary isometric contractions (MVC) of the biceps were recorded at four time points (i.e., baseline; post 1: immediate after cupping-fatigue/fatigue-cupping interventions; post 2: 3 h after cupping-fatigue/fatigue-cupping interventions; post 3: 6 h after cupping-fatigue/fatigue-cupping interventions). Two nonlinear sEMG indexes (sample entropy, SampEn; and percent determinism based on recurrence quantification analysis, %DET) were used to evaluate the recovery from exercise-introduced muscle fatigue. The Friedman test followed by the Nemenyi test and the Mann-Whitney U test were applied in statistics. Results The SampEn and %DET change rate did not show any significant differences at four time points in the pre-condition group. However, there were significant delayed effects instead of immediate effects on improving muscle fatigue in the post-condition group (SampEn change rate: baseline 0.0000 ± 0.0000 vs. post 2 0.1105 ± 0.2253, p < 0.05; baseline 0.0000 ± 0.0000 vs. post 3 0.0627 ± 0.4665, p < 0.05; post 1–0.0321 ± 0.2668 vs. post 3 0.0627 ± 0.4665, p < 0.05; and %DET change rate: baseline 0.0000 ± 0.0000 vs. post 2–0.1240 ± 0.1357, p < 0.01; baseline 0.0000 ± 0.0000 vs. post 3 0.0704 ± 0.6495, p < 0.05; post 1 0.0700 ± 0.3819 vs. post 3 0.0704 ± 0.6495, p < 0.05). Moreover, the SampEn change rate of the post-condition group (0.1105 ± 0.2253) was significantly higher than that of the pre-condition group (0.0006 ± 0.0634, p < 0.05) at the post 2 time point. No more significant between-groups difference was found in this study. Conclusion This is the first study demonstrating that both the pre-condition and post-condition of cupping therapy are useful for reducing muscle fatigue. The post-condition cupping therapy can e ffectively alleviate exercise-induced muscle fatigue and there is a significant delayed effect, especially 3 h after the interventions. Although the pre-condition cupping therapy can not significantly enhance muscle manifestations, it can recover muscles into a non-fatigued state.